The role of lifestyle changes in gastroesophageal reflux diseases treatment - Dağlı, Ülkü; Kalkan, İsmail Hakkı (Turkish Journal of Gastroenterology, 2017)
Abstract Lifestyle modification has an important role in the treatment of gastroesophageal reflux disease (GERD). The development of GERD symptoms with various foods shows individual differences. Although there is not enough evidence that certain substances in a diet could lead to GERD symptoms, the literature suggests that there might be a relationship between reflux development and salt, salted foods, chocolate, fatty foods, and fizzy drinks. Because lying on the left side and raising the head of the bed in a supine position reduces the development of nocturnal reflux symptoms, the head should be elevated for patients with reflux symptoms at night, and the patient should lie on the left side. Smoking and obesity (especially abdominal) trigger GERD symptoms. Whereas excessive physical activity is a significant risk factor for the development of GERD, regular and mild-moderate physical activity has been shown to reduce the symptoms of reflux. Cite this article as: Dağlı Ü, Kalkan İH. The role of lifestyle changes in gastroesophageal reflux diseases treatment. Turk J Gastroenterol 2017;28(Suppl 1); S33-S37 Full Text Turkish